DETERMINAN FLUKTUASI INVESTASI ASING (FOREIGN DIRECT INVESTMENT) DI INDONESIA: ANALISIS MAKROEKONOMI DAN INDEKS SAHAM GLOBAL - Tanti Febi Setiawan; Tri Gunarsih (Jurnal Ilmu Manajemen, 2023)
This research examines the impact of macroeconomic and global equity indices on Indonesian Foreign Direct Investment (FDI) volatility. Macroeconomic variables comprise Indonesia's rate of inflation and trade of balance. The Global Equity Index includes of Hang Seng Index (HSI) and Dow Jones Industrial Average (DJIA). This research uses annual data from 1970 to 2020. The Vector Error Correction Model (VECM) was implemented to test the hypotheses. The results show that the inflation rate did not impact short-term FDI. However, the trade balance, HSI, and DJIA had negative and negligible impacts on FDI in Indonesia. The results also show a positive effect between the inflation rate and the balance of trade on FDI in the long run. However, the HSI hurts FDI in Indonesia, while the DJIA positively affects FDI. The research shows that in the short term or long term, a country needs to consider new terms for investment, especially for foreign countries. In a short time, a country can manage its terms in the balance of trade and feel to observe the fluctuations of HSI and DJIA because these variables negatively impact FDI, which causes a decrease in the balance of trade, and a downward change in HSI and DJIA will increase FDI and vice versa. In the long term, considering managing the duration of inflation and balance of trade, observing DJIA will positively boost FDI fluctuations. Conversely, down changes in HSI will increase the FDI.